Probing MeV to 90 GeV axion-like particles with LEP and LHC - Joerg Jaeckel; Michael Spannowsky (Physics Letters B, 2016)
Axion-like particles (ALPs), relatively light (pseudo-)scalars coupled to two gauge bosons, are a common feature of many extensions of the Standard Model. Up to now there has been a gap in the sensitivity to such particles in the MeV to 10 GeV range. In this note we show that LEP data on Z→γγ decays provides significant constraints in this range (and indeed up to the Z-mass). We also discuss the sensitivities of LHC and future colliders. Particularly the LHC shows promising sensitivity in searching for a pseudo-scalar with 4≲ma≲60 GeV in the channel pp→3γ with m3γ≈mZ.